168k views
5 votes
-2(x + 3) = -2(x + 1) - 4
A 2
B3
C all real numbers
D no solution

1 Answer

1 vote

Answer:

Answer is D (no solution)

Explanation:

-2(x + 3) = -2(x + 1) - 4 --------multiply what's on the outside with everything on the inside

-2x - 6 = -2x - 2 - 4 -----collect like terms

-2x + 2x = 6 - 2 - 4 --------- add/subtract

0 = 4 - 4

0 = 0

User Frank Wiles
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.